PENGEMBANGAN MIND MAPPING BERBASIS 3 DIMENSI PADA KELAS IV MI TARBIYATUL AULAD WEDANI - Indah Dwi Lestari; Arya Setya Nugroho; Nanang Khoirul Umam (Universitas Muhammadiyah Gresik, 2021)
His study aims to determine the development of 3-dimensional mind mapping in class IV Mi tarbiyatul aulad wedani, and determine the validity of 3-dimensional mind mapping based on class IV Mi tarbiyatul aulad Wedani. The study was conducted at MI Tarbiyatul Aulad Wedani Cerme. The model used is a model developed by Thiagarajan which is a 4-D model with the modification of researchers into three stages including the stages of defining, designing, and developing. The final results of the validator assessment of mind mapping based on 3 dimensions in class IV MI Tarbiyatul Aulad Wedani is 86.65 and included in the category very feasible to be used in the learning process of class IV MI Tarbiyatul Aulad Wedani students.